Some methods and strategies for maintaining and enhancing workers' mental and physical health in the work environmenty - SERIR, Faroudja (Al-Jamie Journal In Psychological Studies and Educational Sciences, 2023)
Health in the work environment is one of the concerns of employers and managers of institutions, due to the negative effects on both the worker and the institution. As for the worker, it causes psychological and physical damage to him. As for the institution, it causes material and human damages to production, machinery and work means in general, compensation for injured workers from work accidents and various occupational diseases ... etc. Therefore, most organizations have focused on providing a healthy work environment by relying on a set of strategies and methods to preserve and enhance mental and physical health of workers. Employers and managers of institutions must pay attention to the psychological and physical health of workers in various organizations and consider the various problems and difficulties they receive in their work environment by researching the most important strategies to maintain mental and physical health, as well as paying attention to promoting health at work by improving the material, organizational and social working conditions of workers in their work environment, and paying more attention to the psychological aspect of the worker by raising his morale with material and moral incentives, and eliminating the causes of anxiety, depression and various pressures that He suffers from it, by opening the door for discussion and dialogue between the worker and the management, listening to his various problems and concerns, and trying to solve them with the help of various specialists (psychologists, labor doctors, ergnomes... Etc. Accordingly, this study aims to review some of the methods and strategies followed by institutions in maintaining and promoting the mental and physical health of workers in the work environment. What does it represent?